Bias for Vocalic Over Consonantal Information in 6‐Month‐Olds. (26th July 2017) - Hochmann, Jean‐Rémy; Benavides‐Varela, Silvia; Fló, Ana; Nespor, Marina; Mehler, Jacques
Abstract : Human languages rely on the ability to learn and produce an indefinite number of words by combining consonants and vowels in a lawful manner. The categorization of speech representations into consonants and vowels is evidenced by the tendency of adult speakers, attested in many languages, to use consonants and vowels for different tasks. Consonants are favored in lexical tasks, while vowels are favored to learn structural regularities. Recent results suggest that this specialization is already observable at 12 months of age in Italian participants. Here, we investigated the representations of younger infants. In a series of anticipatory looking experiments, we showed that Italian 6‐month‐olds rely more on vowels than on consonants when learning the predictions made by individual words (Experiment 1) and are better at generalizing a structure when it is implemented over vowels than when it is implemented over consonants (Experiments 2 and 3). Until 6 months of age, infants thus show a general vocalic bias, which contrasts with the specialization previously observed at 12 months. These results suggest the format of speech representations changes during the second semester of life.